Applied geophysics on a soil contaminated site by chromium of a tannery in motuca (SP) - Helene, Lívia Portes Innocenti [UNESP]; Moreira, César Augusto [UNESP]; Carrazza, Leonardo Paioli [UNESP] (My University, 2016)
The management of contaminated sites includes the purchase of a data set ranging from the historical information of the occurrence, preliminary and detail diagnostic, monitoring and remediation. The settlement Monte Alegre located in Motuca (SP) received an irregular disposal of waste of tannery leather on the soil surface in 2001 by the industries of the region. The tanning process involves the use of chromium salts, considered a carcinogen element in its hexavalent form. Based on preliminary evidence, the Environmental Agency of São Paulo State (CETESB-Companhia Ambiental do Estado de São Paulo) performed chemical analysis and recognized soil contamination in some lots. This study conducted geophysical surveys at one of these lots, the one that received the higher amount of leather (40 tons). The geophysical methods of resistivity and induced polarization conducted by 10 parallel lines of electrical tomography of Schlumberger array were used. The analysis of the environmental history of the field and geophysical results to characterize the presence of metal contaminants (Cr) in soil, which receive leather, indicated high chargeability (above 0.67 mV/V). More than one decade from the end of the disposal, it is still recognized clear indications of contamination in the soil by chromium, possibly due to its dissolution in rainwater, infiltration into the soil and complexion/retention by clay minerals.
Keywords: 3D modeling; Chargeability; Contamination; Leather; Resistivity